Describing the resistance patterns of necrotising fasciitis in Acute Care Surgery - Mabogoane, Tumiso (University of Cape Town, 2020)
Objective: This study aims to identify the microorganisms and antibiotic resistance patterns in necrotising fasciitis. Methods: This is a retrospective audit over two consecutive years (June 2015 - July 2017) of all patients who had surgery for necrotising fasciitis at an ACS unit. Results: Necrotising fasciitis accounted for 15% of all skin and soft tissue sepsis that required surgery. There were 10 male (52.6%) and nine female (47.4%) patients. The most common co-morbidity was diabetes mellitus in 10 (52.6%) patients, the compliance and control were monitored by glycosylated haemoglobin (HbA1C) in 50% of the diabetic group, with a mean of 8.98 (Range 5-12.9). Fifteen percent of cases (n=3) had a confirmed diagnosis of HIV, with a negative result in eight (42%). ICU was required in three patients two of whom were on inotropes and one patient required renal replacement therapy. Surgery was performed within 24 hours for 11 (57%) patients. The most common anatomical site for debridement was perineum in nine patients (47%). Monomicrobial infection was the most common subtype of necrotising fasciitis with methicillin sensitive staphylococcus aureus in five (26%) as the predominant microbe. Gram-negative organism Escherichia-coli was the second most common monomicrobial infection. All Gram-positive organisms were sensitive to cloxacillin and coamoxiclavulanic acid. Two gram negatives(15%) of the 13 organisms cultured were resistant to co-amoxiclavulanic acid. The 30 day mortality was 15%. Conclusion- Necrotising fasciitis is a rare but lethal infection. In our limited series, monomicrobial infection is the most common subtype. 15% of the community acquired organisms were resistant to the empiric antibiotic of choice co-amoxiclavulanic acid.